Mẫu mã sản phẩm ảnh hưởng đến tiết kiệm vật liệu trong sản xuất xây dựng - Bùi, Văn Yêm (Bộ Giáo dục và Đào tạo, 2013)
This article presents money losses in building. The losses of construction are caused by government regulations. Briefly, the information in this article is expected to help construction material producters, new building owerners to be.